Bangladeshi consumers' purchasing intention towards organic meat - Prince, Sheikh Ashiqurrahman; Donyaprueth Krairit; Badir, Yuosre; Thammarat Koottatep (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
According to the reports of food and agriculture organizations, about 45 million people (Ahmed, 2014) in Bangladesh suffer from food-borne diseases or food poisoning. Aspects of the green movement include ecological thinking and sustainability (Dangelico and Pontrandolfo 2010), which are the same basis of organic food. Organic meat is considered good for health, and the government (Naranjilla and Kaur, 2015) has emphasized the importance of this issue. Therefore, many parties support the consumption of organic meat. The purpose of this study is to investigate how Bangladeshi consumers' psychological interpretation of organic meat's attributes stimulates their intention to purchase the meat. From the literature review, the study gathered theories and concepts and identified attributes of consumers' psychology about organic meat. Based on the literature review, the researcher developed a conceptual model of the study. The model depicts consumers' cognitive and affirmative factors combined with the attributes of organic meat. This combination of factors, in turn, affects their intention to purchase the meat, based on the theory of cognitive dissonance. Among the 14.6 million residents in Dhaka, the study has selected respondents based on stratified sampling that covers low, middle and higher income groups of consumers to represent the entire population. The study included 320 selected samples that have been analyzed through a series of statistical analyses such as Cronbach's alpha, test of normality, exploratory factor analysis, confirmatory factor analysis and structural equation modelling. The study finds that consumers' cognitive and affirmative interpretations of organic meat's health benefits, verbal recommendations, purchase convenience and availability are statistically significant and positively affect consumers' intention to purchase such meat in Bangladesh. However, consumers' cognitive and affirmative interpretation of organic meat's price is not significant does not affect consumers' intention to purchase the meat. The study also suggests that consumers' age, gender, number of children and regular habit of purchasing organic meat significantly influence them toward the intention to purchase the meat in Bangladesh. The empirical findings of the study could guide stakeholders to select the appropriate target market and apply necessary strategies such as price reduction, advertisement and other promotional activities to develop of the organic meat market in Bangladesh.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management, School of Management
Thesis (Ph.D.) - Asian Institute of Technology, 2017
Keywords: Consumers -- Psychology; Natural foods -- Economic aspects